2010
DOI: 10.1590/s0100-83582010000400022
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre densidade de plantas e genótipos de soja roundup readyTM

Abstract: RESUMO -A presente pesquisa teve por objetivo estudar a influência de diferentes densidades de plantas e genótipos de soja Roundup Ready™ (RR) em algumas características morfoagronômicas da soja, semeada em duas safras distintas. O experimento foi conduzido na região dos Campos de Cima da Serra, no Estado do Rio Grande do Sul, nas safras agrícolas 2006/07 e 2007/08, com os cultivares CD 213RR e BRS 255RR, nas densidades de 12, 18, 24, 30 e 36 plantas aptas por m 2 . O delineamento experimental utilizado foi de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
2
14
1
12
Order By: Relevance
“…These results showed that the plant densities at harvest were well below the desired densities at sowing. These findings were in agreement with the results of Cox and Cherney (2011) and Suhre et al (2014). These authors reported that many biotic and abiotic factors, such as machinery malfunction, seed diseases, soil compaction and hail rain, interfere in the establishment of a stand.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results showed that the plant densities at harvest were well below the desired densities at sowing. These findings were in agreement with the results of Cox and Cherney (2011) and Suhre et al (2014). These authors reported that many biotic and abiotic factors, such as machinery malfunction, seed diseases, soil compaction and hail rain, interfere in the establishment of a stand.…”
Section: Resultssupporting
confidence: 91%
“…We observed a linear reduction in the percentage of green seeds with an increase in the seeding rate. In contrast to what was hypothesized, an increase in the intraspecific competition caused by a higher plant density (SOUZA et al, 2010), especially when associated with water and thermal stress, did not provoke forced maturation of the seeds, causing the retention of chlorophyll in the cotyledons. This result reinforces the aforementioned theory that supported the production of larger seeds at high plant densities, since the best water supply at high densities prevented the forced degradation of chlorophyll, and thus, the In the 2013/14 crop, the occurrence of green seeds was affected by the seeding rate ( Figure 5) and seed size (Table 1).…”
Section: Evaluation Of the Mass Of One Thousand Seeds And The Percentcontrasting
confidence: 82%
“…Plant spatial arrangement is determined by plant density and row spacing, and a change in these elements may increase grain yield, without a major impact in production cost (Souza et al 2010). Plant density affects intraspecific competition for water, light and nutrients and may alter plant architecture, the use of environmental resources and phytosanitary management (Procópio et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies considering cultivars with indeterminate growth habit, development cycle shorter than 120 days and plants with low size and compact architecture -attributes increasingly desired in soybean genetic breeding programs (Souza et al, 2010). Another factor that influences soybean growth and yield is the supply of nitrogen (N).…”
Section: Introductionmentioning
confidence: 99%